HYDROLOGICAL CHARACTERISTICS THAT DETERMINE SUSPENDED SEDIMENT LOAD OF TROPICAL URBAN STORM EVENTS - Lama, Daryl (Malaysian Journal of Science, 2011)
Dwelling on the less investigated tropical urban river channels, this paper attempts to understand the hydrological characteristics that dominate and account for most of the suspended loads of individual events through intra-events SS concentrations-Discharge (Q) relationship. Individual storm event has a variable signature due to the differing hydrological characteristics. As such, suspended sediment (SS) loads transported during storm events are never equivalent. A total of 34 storm events were determined from four gauging stations in the Kallang subcatchment, of the Marina Barrage Catchment, Singapore. There is a need for authorities to understand the nature of storm dynamics for optimal management of water resources in the new reservoir’s catchment. Step-wise regression model was used to determine the dominating hydrological characteristics of the total loads during the storm events. Peak SS concentrations and the duration of high rainfall intensity (>60mm/h) are the main determinant of SS loads in the tropical urban waterways. Rapid rising and falling limbs of the storm hydrograph and short, intense storm events, typical of tropical, urban environment are explanations for the outcomes attained from the regression analysis. (Keywords: Tropical urban catchment, Suspended Sediment, Discharge, Regression modeling, Hydrological Characteristics ) INTRO